Thoracic non-osseous lesions in cancer patients detected in low-dose CT images acquired as part of skeletal SPECT/CT examinations - Wuest, W.; Lell, M.; May, M. S.; Saake, M.; Kuwert, T.; Uder, M.; Linke, R. (Nuklearmedizin - NuclearMedicine, 2015)
Aim: Hybrid single-photon emission tomographic (SPECT) and X-ray computed tomography (CT) systems are increasingly used in oncologic imaging. With SPECT/CT not only the thoracic spine but also the surrounding soft tissue needs to be evaluated for pathological findings. The purpose of this study was to assess the prevalence of non-osseous findings detectable on low-dose CT datasets from patients studied by thoracic 99mTc-dicarboxypropane diphosphonate (DPD)-SPECT/CT. Patients, methods: 119 consecutive oncologic patients (81 breast cancer, 38 with other cancer) who underwent DPDSPECT CT of the thoracic region were included in this study. Non-osseous findings on CT were classified as either probably benign or suspicious. Suspicious findings were correlated with retrievable previous imaging and if performed with follow up imaging (MRI, CT with contrast medium, Ultrasound) or biopsy results. Results: In 80/119 (67%) patients no imaging was performed before SPECT/CT. Only 7/119 subjects (6%) had no other lesions than bone lesions. In 101/119 (85%) patients lesions found on SPECT/CT images were rated as benign and in 65/119 (55%) patients as suspicious. In 8/119 (7%) patients with previously unknown suspicious lesions on SPECT/ CT images suspicious findings were confirmed by biopsy. Conclusion: 7% of patients referred to SPECT/CT of the thoracic spine for staging of malignant disease had previously unknown suspicious non-osseous lesions detectable on the low-dose CT images which were confirmed by biopsy. This could be especially relevant for cancer entities like breast and prostate, in which no thorax-CT is routinely intended for staging.
Keywords: Non-osseous suspicious lesions; skeletal SPECT/CT; incidental findings; low-dose thorax CT images